PENINGKATAN EFISIENSI MANAJEMEN KEUANGAN MELALUI PENDAMPINGAN SISTEM INFORMASI KEUANGAN MADRASAH - Sulistiyani, Endang; Khusnah, Hidayatul; Magfira, DikeBayu; Maulana, Muchsin; Affandi, Muhammad Nizar; Fuady, Muhammad Farhan; Putra, M Wava Ferdiansyah (Jurnal Abdi Insani, 2025)
Yayasan Pondok Pesantren Nurul Huda is an Islamic educational institution facing challenges in financial management due to a manual bookkeeping system prone to errors and delayed reporting. To address this issue, a community engagement program was conducted to implement a digital financial information system that is efficient, accurate, and tailored to the institution's needs. The method employed a collaborative approach involving three main stages: preparation, implementation, and evaluation. Initial mapping of financial processes was followed by system development and user training, then concluded with a usability evaluation. The program resulted in a functional digital financial information system supporting income, expenditure, student savings tracking, and report generation in both print and graphical formats. The system includes structured user roles and menus aligned with the foundation's organizational workflow. Usability testing using the SUS questionnaire with 23 respondents yielded an average score of 63.48, classified as “OK, Marginal, Passive” indicating the system is usable but requires interface improvements and continued support. This initiative significantly enhanced financial data management efficiency and strengthened digital literacy among foundation staff.